2022
DOI: 10.4269/ajtmh.22-0214
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Evaluate COVID-19 Preventive Hygiene Programs: Observed Mask Wearing, Handwashing, and Physical Distancing Behaviors in Public Indoor Spaces in Democratic Republic of the Congo

Abstract: The objective of our study was to develop and test observational methods to evaluate COVID-19 preventive hygiene behaviors and physical distancing, and to evaluate the effectiveness of a government mandate on indoor fully covered mask wearing. An observational study was conducted of 4,736 individuals from April to October 2021 using 5-hour and rapid (10-minute) structured observations and spot checks to evaluate mask-wearing, handwashing, and physical-distancing behaviors, and the functionality of handwashing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Even during enforcement of the mask mandate, it was noted that individuals were often not wearing their mask over both their nose and mouth. This is also consistent with our quantitative study which found that only 16% of >4600 observed individuals wore a mask completely covering their nose and mouth in indoor public spaces (George et al, 2022, In press) [ 27 ]. Engaging local leaders (e.g., religious leaders, community healthcare workers, and school officials) in raising awareness about mask wearing can help to increase compliance.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Even during enforcement of the mask mandate, it was noted that individuals were often not wearing their mask over both their nose and mouth. This is also consistent with our quantitative study which found that only 16% of >4600 observed individuals wore a mask completely covering their nose and mouth in indoor public spaces (George et al, 2022, In press) [ 27 ]. Engaging local leaders (e.g., religious leaders, community healthcare workers, and school officials) in raising awareness about mask wearing can help to increase compliance.…”
Section: Discussionsupporting
confidence: 92%
“…Community participants mentioned that the handwashing stations in public places often lacked water and cleansing agents. This is consistent with our parallel quantitative study which found that the majority (61%) of handwashing stations in indoor public spaces (e.g., entrances of health facilities, schools, and universities) in Bukavu did not have both water and handwashing agents present (George et al, 2022, In press) [ 27 ]. Community residents interpreted the lack of upkeep of handwashing stations and relaxing of masking mandates as meaning that COVID-19 transmission was less of a concern.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations